2022
DOI: 10.3390/ma15093016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Fly Ash and Ground Granulated Blast Furnace Slag Content on Concrete Properties: Experiments and Modelling

Abstract: Concrete is known as the most globally used construction material, but it releases a huge amount of greenhouse gases due to cement production. Recently, Supplementary Cementitious Materials (SCMs) such as fly ash and Ground Granulated Blast Furnace Slag (GGBFS) have been widely used in concrete to reduce the cement content. However, SCMs can alter the mechanical properties and time-dependent behaviors of concrete and the early age mechanical properties of concrete significantly affect the concrete cracking in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Beyond 800 • C, recrystallization of amorphous silica to tridymite and cristobalite occurred, and more prism-shaped particles were observed in the micrograph of calcined SBA samples. In addition, the microstructural properties of RH-SiO 2 , as displayed in Figure 9, revealed that the particles contained porous, angular, cellular, and irregular shapes and textures [112,113]. The reactive amorphous silica can have a cellular structure; the samples that were cellular and porous contained greater surface area, thereby having greater water-absorption features.…”
Section: Industrial-agro-waste Ashes-based Aab Microstructural Proper...mentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond 800 • C, recrystallization of amorphous silica to tridymite and cristobalite occurred, and more prism-shaped particles were observed in the micrograph of calcined SBA samples. In addition, the microstructural properties of RH-SiO 2 , as displayed in Figure 9, revealed that the particles contained porous, angular, cellular, and irregular shapes and textures [112,113]. The reactive amorphous silica can have a cellular structure; the samples that were cellular and porous contained greater surface area, thereby having greater water-absorption features.…”
Section: Industrial-agro-waste Ashes-based Aab Microstructural Proper...mentioning
confidence: 99%
“…Figure 9. Residual ashes' SEM micrographs (a) FA[113], (b) GGBFS[113], (c) SBA[93], (d) RH-SiO₂, (e) POA[97] and (f) SA[116] Figure9. Residual ashes' SEM micrographs.…”
mentioning
confidence: 99%
“…Concrete is a composite material consisting of water, cement, and coarse aggregates. e special properties of the composite material determine its macroscopic mechanical properties [1]. e destruction process involves the interaction of various scales, from the microscopic to the macroscopic [2,3] .…”
Section: Introductionmentioning
confidence: 99%
“…SCMs have been widely used in concrete to reduce cement content (consequently decreasing CO 2 emission) and improve the mechanical and durability performance of concrete 29 . In addition, SCMs are mainly industrial by‐products, so more economical than cement.…”
Section: Introductionmentioning
confidence: 99%
“…9,[26][27][28] SCMs have been widely used in concrete to reduce cement content (consequently decreasing CO 2 emission) and improve the mechanical and durability performance of concrete. 29 In addition, SCMs are mainly industrial byproducts, so more economical than cement. However, SCMs also have drawbacks, such as decreasing the early age strength development and impacting the viscoelastic properties like tensile creep.…”
Section: Introductionmentioning
confidence: 99%